Gifted around the globe : gifted and talented education in international schools : a thesis in partial fulfillment of the requirements for the degree of Master of Education at Massey University, Manawatu, New Zealand - Begg, Kylie (Massey University, 2012)
Gifted education in international schools is an area that is yet to be fully investigated. The aim of this study was to explore the ways in which international schools identify gifted students and provide for their individual needs. Issues for international schools that were identified in the literature review included: cultural and linguistic diversity of students and the community, high teacher and student mobility and availability of provisions. A multiple case study design was used. Nineteen international schools from Europe, Asia and the Middle East were invited to participate in the study; however, only two schools participated in the study. The guiding principles, identification procedures and range of provisions were explored through an examination of relevant documentation, interviews with three staff members from each school, and a questionnaire presented to all teaching staff. The findings were analysed using a cross case procedure and pattern matching. The findings of the study indicate that the definitions and policy document created by the school are important for shared understandings of giftedness. Staff expertise and attitudes towards identifying gifted students from diverse cultures may impact the effectiveness of the school’s gifted programme. In both schools a tension between retaining the home-country’s ethos and internationalism and inclusivity was identified through the schools’ use of some culturally biased assessment practices, and little planning for culturally and linguistically diverse students. Finally, staff and student mobility was found to have an impact on the effectiveness of identification and practices for provision. Recommendations for international schools include: creating a definition and policy suited to the school; creating opportunities for professional development, and making links with the school and wider community. The findings of this study are limited due to the small number of case studies used. It is suggested that similar research is undertaken with a larger and more diverse group of schools.
Keywords: Gifted children; Gifted students; Cross-cultural studies; Education